EVALUASI PROGRAM PENDIDIKAN DAN PELATIHAN PENINGKATAN KOMPETENSI PEDAGOGIK GURU SMK DI PUSAT PENGEMBANGAN PEMBERDAYAAN PENDIDIK DAN TENAGA KEPENDIDIKAN (PPPPTK) MEDAN - SIMANJUNTAK, WANTI (Unversitas Katolik Santo Thomas, 2020)
This study aims to describe: (1) the context of education and training programs to improve pedagogical competence in PPPPTK Medan; (2) input of education and training programs to improve pedagogical competence in PPPPTK Medan; (3) the process of education and training programs to improve pedagogical competence in PPPPTK Medan; (4) the results of education and training programs to improve pedagogical competence in PPPPTK Medan. This research is an evaluation research with a qualitative approach. The subjects of this study were education and training providers, widyaswara education and training programs for improving pedagogical competencies, training participants for improving pedagogical competencies in 2019. Data collection techniques used non-participant observation, interviews, and documentation studies. Data validity test is done by triangulating methods and data sources. Data analysis uses qualitative analysis of Miles and Huberman's model. The results of the study show the following. (1) The context of the Medan PPPPTK education and training program has fulfilled the existing requirements in government regulations regarding the implementation of education and training. The training provider needs to analyze the training target (participants) in accordance with the training objectives. (2) Enter the training program, that the curriculum is relevant to the needs and objectives of the training. The training organizer has analyzed the level of training needs of Pedagogical Competency Improvement participants according to the participants' interests. Education and training facilities available are able to support the implementation of education and training. (3) The process of the education and training program, which is related to the learning media used, has not yet fully supported the implementation of the training. Teaching methods applied by teachers have not been implemented as planned. The implementation of the training was in accordance with the training schedule, but the material had not been conveyed to the fullest so there was a need for additional training time. (4) the quality of graduates from PPPPTK Medan can implement their pedagogical competencies. The number of graduates in 2019 has met the target of graduates